The relationship between working capital and firm performance in Malaysia - Rajespari, Kumar (2019)
The study investigated the relationship between working capital and firm performance of 272 listed firms in Malaysia for 2012 – 2016. The dependent variable to measure firm performance is Return on Asset (ROA). The independent variable used in this research are Average collection period (ACP), Inventory conversion period (ICP), Average payable period (APP), Cash conversion cycle (CCC) and Current Ratio (CR). Findings of the panel data regression reveal that Average collection period and Inventory conversion period are significantly negatively correlated to firm performance. This suggests that the shorter the period, the higher the firm performance among firms in Malaysia. However Average payable period, Cash conversion cycle and Current ratio is significantly and positively correlated to firm performance. This suggests that the longer the firm delays payment to creditors, the higher will be firm performance through the utilization of opportunity cost. The findings of this study assert that in general, Malaysian firms are seems to make short term decision when it comes to managing their working capital and cash cycle. Among all the components of working capital, firm choose to stretch their payables. For future studies, researchers are recommended to look into the requirement of working capital based on industry and examine its impact on firm performance.